The Influence of Planning and Volition on E‐Learning Utilization During Technology Transitions - Seiberling, Christian; Kauffeld, Simone (International journal of training and development, 2025)
ABSTRACT The purpose of this study was to identify factors linked with e‐learning utilization. This empirical study (N = 381) was conducted in partnership with a German bank and measured e‐learning utilization as the degree to which participants thoroughly completed an extensive number of automatically provided e‐learning courses on new banking software. The results suggest that e‐learning utilization is influenced by the workplace context in which e‐learning takes place (supervisor support, personal capacity for learning), the planning of the learning process, and a learner's volition to learn. Planning the e‐learning process mitigated an unfavourable learning environment in terms of limited time resources for learning to some extent.